The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.2165/00003088-197803040-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Sulphamethoxazole in Man

Abstract: A high performance liquid chromatography method for the determination of sulphamethoxazole and its metabolite N4-acetylsulphamethoxazole is described. The renal excretion rate and cumulative renal excretion of sulphamethoxazole is markedly influenced by urinary pH. With constant urinary pH, the renal excretion rate and the renal clearance of sulphamethoxazole is dependent on the urine flow. The renal clearance of the metabolite N4-acetylsulphamethoxazole is not influenced by urinary pH or urine flow. No clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
6

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 21 publications
0
17
0
6
Order By: Relevance
“…5 per cent (SEM) and its metabolite 93.2+ 1. 8 per cent (SEM). It can be concluded that protein binding of parent compound and metabolite is not different in 'fast' and 'slow' acetylators (p = 0.1 5).…”
Section: Protein Bindingmentioning
confidence: 97%
“…5 per cent (SEM) and its metabolite 93.2+ 1. 8 per cent (SEM). It can be concluded that protein binding of parent compound and metabolite is not different in 'fast' and 'slow' acetylators (p = 0.1 5).…”
Section: Protein Bindingmentioning
confidence: 97%
“…Several HPLC methods have been reported for determination of amoxicillin [1,2,4,[5][6][7][8][9][10], penicillin G [11][12][13], penicillin V [13,14], ampicillin [1,3,6,15,[16][17][18][19][20][21], oxacillin [22], cloxacillin [13,15,, nafcillin [22] and dicloxacillin [13,22,23] in biological fluids. A few methods describe determination of two [6,15,23], or at most 4 [13,22], of these penicillins.…”
Section: Introductionmentioning
confidence: 99%
“…A few methods describe determination of two [6,15,23], or at most 4 [13,22], of these penicillins. Sample preparation techniques reported for plasma or serum include dilution [23], ultrafiltration [6, t 3, 16], deproteinisation with trichloroacetic acid [3,17,21], perchloric acid [1,4] or methanol [15], deproteinisation with perchloric acid and dichloroethane [2], deproteinisation with acetonitrile and extraction with dichloromethane [22,25], deproteinisation with trichloroacetic acid followed by derivatisation and extraction with diethyl ether [17], extraction with dichloromethane from acid solution [23,24], SPE of diluted sample [7,10,12,14,16,20], deproteinisation with sulphuric acid and sodium tungstate followed by SPE [11], on-line dialysis and SPE of buffered samples [8] and column-switching techniques on diluted or deproteinised samples [4,9,18,19]. in most cases ultraviolet (UV) detection is at wavelengths close to 230 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers on the HPLC assay of co-trimoxazole [21,22] suggested direct reversed-phase chromatography of serum and plasma following protein precipitation. This simplified sample preparation is preferred by many analysts because it is fairly fast and useful in special situations, such as are encountered in toxicological hospital laboratories and emergency rooms.…”
mentioning
confidence: 99%
“…The low concentration of pertinent substances makes the sensitivity by this method [21] too low for pharmacokinetic studies. Bury's paper [22] describes a procedure requiring two different chromatographic determinations for SMZ and TMP respectively (excluding the SMZ N4-acetyl metabolite), necessitating two chromatographic instruments or extended analysis times.…”
mentioning
confidence: 99%